2001
DOI: 10.1063/1.1377323
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting MgB2 films via precursor postprocessing approach

Abstract: to 39 K in these reports. Here, we report our successful demonstration of the growth of 3 superconducting MgB 2 films using electron beam evaporated B precursor films followed by appropriate post-annealing. We also report results of transport property measurements on these ex-situ grown MgB 2 films. The MgB 2 films had a sharp T c (zero resistance) of 38.0 K with a ∆T c of 0.3 K and a ratio of the room temperature resistivity to the residual resistivity above T c of about 2. The resistivity decreased linearly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 9 publications
4
89
0
Order By: Relevance
“…Most reports on magnesium diboride (MgB 2 ) thin-film preparation techniques describe a process that requires postdeposition annealing to produce superconducting films. [6][7][8][9][10][11][12] However, as-grown superconducting thin films are favorable for applications utilizing, for instance, Josephson junctions. Two groups 13,14 reported as-grown superconducting MgB 2 films, however, those films showed poor crystallinity.…”
Section: Highly Crystallized As-grown Smooth and Superconducting Mgb mentioning
confidence: 99%
“…Most reports on magnesium diboride (MgB 2 ) thin-film preparation techniques describe a process that requires postdeposition annealing to produce superconducting films. [6][7][8][9][10][11][12] However, as-grown superconducting thin films are favorable for applications utilizing, for instance, Josephson junctions. Two groups 13,14 reported as-grown superconducting MgB 2 films, however, those films showed poor crystallinity.…”
Section: Highly Crystallized As-grown Smooth and Superconducting Mgb mentioning
confidence: 99%
“…Whereas in most cases rather elaborate preparation techniques, such as PLD or CVD [3,4,15,16], were employed we will present in this paper a rather easy and simple way of fabricating MgB 2 films on alumina substrates, which resulted in excellent superconducting properties, even at 20 K and in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ion milling on the surface impedance was also investigated: using an Ar + beam (0.5 KV, beam current 16 mA) a nominal 60 nm layer was removed from the surface of film #1B. The motivation for that is the observation that the procedure adopted until now for film synthesis favors the growth of Mg-rich surface layers, as reported by various authors [22,51] and confirmed also by EDX (Energy Dispersive X-ray) analysis.…”
Section: Microwave Surface Impedance: Experimental Results and Discmentioning
confidence: 99%
“…Films were obtained by appropriate postannealing of an electron-beam-evaporated B precursor (500 nm) grown directly on a r-plane Al 2 O 3 single-crystal substrate. After deposition the boron film was subsequently sandwiched between cold pressed MgB 2 pellets, along with excess Mg turnings, packed inside a crimped Ta cylinder and finally annealed at 890 °C for 20-25 min [22]. Typical X-ray diffraction θ-2θ scan shows that samples have the c-axis perpendicular to the surface, whereas the pole figure evidences a random in-plane texture.…”
Section: Samples Preparation and Characterizationmentioning
confidence: 99%